EMERGING TECHNOLOGIES FOR QUALITY AGRICULTURAL EDUCATION DELIVERY IN ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN TERTIARY INSTITUTIONS IN ABIA STATE, NIGIERIA (NAU Journal of Technology and Vocational Education, 2026)
The study examined emerging technologies for quality Agricultural Education delivery in Achievement of Sustainable Development Goals (SDGs) in tertiary institutions in Abia State. The study was guided by three research questions and three null hypotheses. Descriptive survey research design was adopted. The population for the study was 80 comprising 25 Agricultural Educators and 55 final year Agricultural Education students in three tertiary institutions. The population was selected using census sampling technique. The instrument for data collection was a structured questionnaire validated by three experts. The reliability coefficient of 0.81, 0.82 and 0.78 was obtained using Cronbach Alpha statistic.  The data collected were analyzed using Mean and Standard deviation while t-test statistic was used to test the null hypotheses at 0.05 level of significance. The findings of the study revealed among others that emerging technology tools required for quality Agricultural Education delivery include: Interactive Whiteboard, Google classroom, Flipped classroom, Projectors, Laptop Computer, Smartphones, Internet, Virtual Farms/Labs. Based on the findings, it was recommended that: there is need for United Nations Educational, Scientific and Cultural Organization to collaborate with tertiary institutions especially to provide emerging technology tools required for quality Agricultural Education delivery in tertiary institutions for Achievement of Sustainable Development Goals (SDGs).
Keywords: Emerging Technologies; Agricultural Education; Tertiary Institutions; Sustainable Development Goals